Osmotic adjustment in two temperate oak apecies [Quercus pyrenaica Willd and Quercus petraea (Matt.) Liebl] ob the Iberian Peninsula in response to drought - Aranda, I.=700 1 Gil, L.; Pardos, A.
(Es, En)
ilus., 35 ref.
Keywords: REGULACION FISIOLOGICA; OSMOREGULACION; SEQUIA; QUERCUS PETRAEA; QUERCUS PYRENAICA; ESPAÑA; AJUSTE OSMOTICO; MODULO DE ELASTICIDAD